The Attribution of an Arabic Commentary on Naṣīr al-Dīn al-Ṭusī’s Taḥrīr al-Majistī to Shams al-Dīn al-Samarqandī - Taro Mimura (Nazariyat: Journal for the History of Islamic Philosophy and Sciences, 2022)
In this paper, I thoroughly examine the anonymous commentary found in Theology Library (Tehran University) MS 678 on Tūsī’s Tahrīr al-Majistī, which the copyist attributed to Samarqandī in the colophon. I compare its contents and some references to Samarqandī’s Sharh Tahrīr al-Majistī, including a bibliographical note in Hājjī Khalīfa’s Kashf al- ̄unūn, an owner’s note on the front page of Carullah MS 1485 (a manuscript of Nīsābūrī’s Sharh Tahrīr al-Majistī), and Nīsābūrī’s own marginal note recording the name Samarqandī in the autograph of his Sharh Tahrīr al-Majistī. In this way, I establish Faculty of Theology Library MS 678 to be a manuscript of Samarqandī’s Sharh Tahrīr al-Majistī. This identification in turn reveals that Nīsābūrī, in his Sharh Tahrīr al-Majistī, called Samarqandī “an eminent scholar” and quoted Samarqandī’s Sharh Tahrīr al-Majistī several times. Therefore, one can conclude Samarqandī’s Sharh Tahrīr al-Majistī has been very influential on Nīsābūrī when he composed his Sharh Tahrīr al-Majistī.